FRI0626 Analysis of correlation and causes for discrepancy between quantitative and semi-quantitative doppler scores in synovitis in rheumatoid arthritis. (15th June 2017) - Rezaei, H; Klint, E af; Hammer, HB; Terslev, L; D'Agostino, M-A; Kisten, Y; Arnaud, L
Abstract : Background: Doppler US is used for the evaluation of synovitis in RA. The amount of Doppler signals are measured in the synovial tissue according to either semi-quantitative (SQS) or quantitative scoring (QS) methods. None of the SQS has been chosen by consensus so far, and this creates some heterogeneity in US in clinical practice and research. Conversely, a major strength of the QS is to allow objective measurement of Doppler pixels using a continuous numeric scale. Objectives: This study aimed to evaluate the association between SQS 1, 2, and QS 3 in RA patients with active disease. Additionally, to elucidate the reasons for potential discrepancies between SQS and QS assessments, in order to better understand the intrinsic limitations of these methods, Methods: Adult patients with RA and inadequate clinical response to anti-rheumatic therapy were examined with US. Dorsal US of the wrists, MCP and MTP 2–5 were performed. US images with sign of synovitis were collected and the QS was measured. Five assessors blinded to the QS evaluated the images independently, according to either SQS method. Association between QS and SQS was studied using correlations and multilevel models taking into account the clustering of ratings at the rater, patient and joint levels. Based on the cut-offs, the discrepant cases were extracted, and each participant was asked to re-grade his/her own discrepant cases, blinded to the initial SQS grading and original QS, and to provide an explanation for the discrepancy. Then, discrepant images and explanations provided were reviewed in consensus and classified into a limited number of categories Results: Analysis of the 1190 ratings revealed a strong correlation (ρ=0.89, p<0.0001) and significant associations (p<0.0001) between QS and SQS. Correlations between QS and SQS according to Szkudlarek et al. (ρ=0.87, p<0.0001) or Hammer et al. (ρ=0.91, p<0.0001) were similar. A total of 239 (20.1%) images were given a SQS grade that did not match that expected based on initial QS, using predefined cutoffs. Main explanations for discrepancies were different perceived ROI (40.7%) and Doppler pixel count near cutoffs between SQS grades (32.3%). Conclusions: We showed that both SQS methods correlated well with QS to assess synovitis, but SQS methods are intrinsically limited when the Doppler pixel count is close to the cutoffs between the SQS grades. Analysis discrepancies between these methods may help further revision of criteria used to assess disease activity with MSUS in RA. References: Szkudlarek M et al. Arthritis Rheum 2003. Hammer HBet al. Ann Rheum Dis 2011. Qvistgaard E et al. Ann Rheum Dis 2001. Acknowledgements: We would like to thank all the participating patients, rheumatologists and nurses who made this study possible. Disclosure of Interest: None declared